The Problem of Change in Canadian Teacher Education - Hopkins, David (Canadian Journal of Higher Education, 1982)
It is argued that Canadian teacher education is characterized by a paradox - that of change and no change. The cause of this paradox is a delinquency in the pro- cess of implementation; the ability to change at the level of structure is not matched by an ability to change at the level of practice. Explanations are sought as to why this is the case. First, the barriers to change in teacher education are analysed and then a situational analysis exposes tensions in the role of teacher training institutions that inhibit their functioning. Finally, individual differences between institutions are explained by a description of the sagas that tend to acculturate them.